Kompetensi Profesional Guru Rumpun Mata Pelajaran PAI di Madrasah Ibtidaiyah (MIN) II Model Samarinda - Riswadi, Riswadi (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
This research aims to find out how professional teachers of Islamic religious education subjects in the MIN 2 Model Samarinda. This research uses an emics perspective, which is trying to understand, internalize, and describe the professional image of the teacher according to the phenomena and data, so it is also called the phenomenological fact. Data Collection techniques using observations, interviews and documentation, while the data analysis techniques to be used in this study,